2008
DOI: 10.1021/om701237t
|View full text |Cite
|
Sign up to set email alerts
|

A BODIPY−Borane Dyad for the Selective Complexation of Cyanide Ion

Abstract: The coupling of borane as a donor and BODIPY as an acceptor leads to a boron-based receptor (3) that shows a 3-fold enhancement in fluorescence response for the selective sensing of cyanide ion by virtue of intramolecular energy-transfer transitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 50 publications
2
48
1
Order By: Relevance
“…12,13 Another intriguing aspect is that the spectra of doublycomplexed QTB-F and QTB-CN are different from one another. of the anion feature both an electron-deficient tricoordinate organoborane and an electron-rich organoborate moiety linked by a bithiophene unit.…”
Section: Department Of Chemistry Rutgersmentioning
confidence: 99%
“…12,13 Another intriguing aspect is that the spectra of doublycomplexed QTB-F and QTB-CN are different from one another. of the anion feature both an electron-deficient tricoordinate organoborane and an electron-rich organoborate moiety linked by a bithiophene unit.…”
Section: Department Of Chemistry Rutgersmentioning
confidence: 99%
“…[9][10][11][12] In 2008, Lee et al first reported the synthesis of a borane-BODIPY conjugate and its applications as a selective sensor for cyanide ion. [9] Later, solid-state emissive features of such borane-BODIPY conjugates were reported by Zhao et al [10] In 2013, our group demonstrated in a number of examples that such multichromophoric borane-BODIPY compounds can show interesting bi-or tri-color emission features, depending on the molecular backbone and structural flexibilities. [12a-d] Although such broad emissive features have been obtained covering large regions of the visible spectrum, dual emissive molecules with emission spanning over visible-NIR regions have not been documented.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Such dyes, usually in the form of boron dipyrromethene (Bodipy) structures, have become extremely popular of late and have formed the basis of numerous opto-electronic devices, sensors, switches and so forth. [16][17][18][19][20] Several Bodipybased molecular dyads are known to undergo extremely efficient electronic energy transfer under UV illumination, although the transfer distances have been kept short, utilising both Fçrster and Dexter mechanisms. [21][22][23] The opportunity to design improved cascade-type arrays centred around Bodipy dyes owes much to the recent introduction of new methodologies for replacement of the B À F bonds, [24] these being an integral feature of conventional Bodipy dyes, with BÀaryl or BÀethynyl bonds.…”
Section: Introductionmentioning
confidence: 99%